2016
DOI: 10.1080/10508422.2016.1172011
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Codes in Sports Organizations: An Empirical Study on Determinants of Effectiveness

Abstract: Confronted with numerous scandals, sports organizations are turning to the adoption of ethical codes to attain more ethical behavior. However, the effectiveness of an ethical code as a means to increase ethical behavior remains debated; furthermore, the particular characteristics of a sports context have not yet been taken into account, nor have the different stages of code establishment been considered in evaluation. This article studies the effectiveness, as measured by the Ethical Climate Index, of ethical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
(102 reference statements)
1
15
0
3
Order By: Relevance
“…The uncovering of this partial trickle‐down effect also offers support for the idea that soccer coaches are of considerable importance regarding the stimulation of an ethical climate in their club (Constandt et al, ; De Waegeneer, ). Previous research has shown that coaches—due to their nearby and influential position—are notably able to promote ethical behavior to their players, both on and off the sporting field (Boardley & Kavussanu, ; Chow et al, ; Delrue et al, ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The uncovering of this partial trickle‐down effect also offers support for the idea that soccer coaches are of considerable importance regarding the stimulation of an ethical climate in their club (Constandt et al, ; De Waegeneer, ). Previous research has shown that coaches—due to their nearby and influential position—are notably able to promote ethical behavior to their players, both on and off the sporting field (Boardley & Kavussanu, ; Chow et al, ; Delrue et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…Although the boards of directors of soccer clubs bear a substantial responsibility concerning the counteraction of abuse and other ethical issues such as doping and match fixing, they often react rather passively (De Waegeneer, ). This passive attitude is even more noteworthy given the potential impact of organizational leadership on the ethical climate in sport organizations (Burton, Welty Peachey, & Wells, ; Constandt, De Waegeneer, & Willem, ).…”
Section: Introductionmentioning
confidence: 99%
“…Posiblemente, uno de los trabajos más recientes que aglutina todos los aspectos recogidos en esta cuestión de la eficacia de los códigos éticos es el de Waegeneer et al (2017), quienes reconocen que es uno de los temas sobre los que sigue siendo necesario que haya más trabajos empíricos, ya que la efectividad de los códigos como instrumentos para mejorar el comportamiento ético sigue siendo Waegeneer et al (2017) recogen en cuatro grandes aspectos los factores determinantes de la efectividad de los códigos: la creación del código, el contenido del código, su implementación y su aplicación. Respecto a la creación hacen referencia a la capacidad del código para guiar la planificación estratégica de la organización y a la necesidad de su revisión, al menos, cada dos años.…”
Section: Contenido Y Gestión De Los Códigos éTicosunclassified
“…Erwin (2011) (2010), Lozano (2007) Las conclusiones de los trabajos de Singh (2011) y de Waegeneer et al (2017) muestran que aún no hay una opinión clara sobre la eficacia de los códigos éticos y de los factores determinantes. Así, por ejemplo, mientras que para Singh (2011) la comunicación del código y la participación de los grupos de interés son determinantes en su eficacia, Waegeneer et al (2017) no encuentran evidencia de esto último. Estas discrepancias corroboran la conveniencia de continuar con investigaciones que sigan profundizando en la gestión de los códigos éticos y en su eficacia.…”
Section: Aspectos De Contenido Y Gestión De Los Códigos Soporte De Launclassified
See 1 more Smart Citation